MIGA 2006 Annual Report - Multilateral Investment Guarantee Agency (Washington, DC: World Bank, 2012)
Contents: Highlights: Fiscal Year 2006 Highlights. Letter from the President to the Council of Governors. Board Activities Highlights. Message from the Executive Vice President. MIGA Officers and Managers. Development Impact: MIGA and Infrastructure: Improving People's Lives. Operational Overview: Guarantees. Technical Assistance. Online Information Dissemination. Legal and Claims. Regional Activities: Asia and the Pacific; Europe and Central Asia; Latin America and the Caribbean; Middle East and North Africa; Sub-Saharan Africa. Independent Evaluation Group and Compliance Advisor/Ombudsman. Management's Discussion and Analysis (FY06) and Financial Statements.